Tradução comentada do português para a Libras da "Cartilha de saúde mental" do INMETRO - Lima, Jocelma Gomes Rodrigues (2023)
This work is part of the field of Translation Studies, more specifically translation and interpreting in public services, also known as Community Interpreting. Authors such as Pöchhacker (2004), Wadensjo (1998), Angelelli (2013), Rodrigues and Santos (2018), Queiroz (2011) and Jesus (2013, 2017) support this dissertation. Mental health is defined by the World Health Organization (2020) as a state of well-being in which an individual realizes his or her own abilities, can cope with everyday stresses, can work productively and is able to contribute to their community. How can this sense of well-being be achieved during a pandemic, where the entire routine has been altered by sanitary impositions, through Decrees, and where security has been threatened? Lives were lost because of a lack of information. There were physical dangers and psychological threats for many. Translation plays an important role in guaranteeing quality and access to contexts that promote mental health, especially for Brazilian communities that are not fluent in Portuguese. Thus, this study proposes an annotated translation from Portuguese into Libras of a booklet produced during the pandemic by the National Institute of Metrology, Quality and Technology (INMETRO) on the subject of mental health. The choice of the booklet genre involving the theme of mental health proved to be relevant, as it presents strategies to develop psychological conditions to deal with daily tasks and demands such as work, relationships and family, among others. The specific objectives are as follows: (i) to understand the extent to which textual and visual information can contribute to more satisfactory translation processes; (ii) to describe linguistic, translation and technological elements that can stand out in the translation process from Portuguese to Libras; (iii) to promote the visibility of the mental health context through translation from Portuguese into Libras, expanding access to knowledge for the deaf community; (iv) to contribute to the prevention of mental suffering and the promotion of mental health; and (v) to collaborate in guaranteeing linguistic rights of access to information, using translation from Portuguese into Libras as a tool. From the first semester of 2022, we defined the theme and the choice of booklet, and in the second semester we recorded a pilot of the project, on which we based our analysis and, finally, we prepared the final version of the translation of the booklet. The methodological approach is qualitative. Descriptive documentary research is used, according to Cellard (2008), especially to understand the phenomenon being studied in its usual environment (SAMPIERI; FERNÁNDEZ-COLLADO; LUCIO, 2006). It is based on a case study, taking the commented translation as a starting point anchored in Nord's Functionalist principles (2016). Throughout the commentedtranslation of Inmetro's Mental Health Booklet, the translation problems and decisions made by the translator are highlighted and examined in the light of Content Analysis (BARDIN, 2016; ROSSI; SERRALVO; JOAO, 2014). Some elements deserve attention, such as linguistic, cultural, visual and technological aspects. Therefore, translation brings cultural aspects as an artifact of the deaf community, which provides identification of the target audience with the way information is passed on, proposing to ensure that the deaf community has this access, thus enabling them to absorb the guidance provided in a light and linguistically comfortable way.